Protein Electrophoresis and Haptoglobin Values for Captive Bongo (Tragelaphus eurycerus) - Bartlett, Susan L.; Lamberski, Nadine; Arheart, Kristopher L.; Cray, Carolyn (Frontiers in Veterinary Science, 2021)
Serum samples collected from 37 clinically normal bongo (Tragelaphus eurycerus) and 13 abnormal bongo were tested using assays for acute phase proteins (APP) and by protein electrophoresis. Abnormal bongo samples (n=27) had significantly higher levels of fibrinogen (FIB) (p <0.001) and trending but not significantly increased haptoglobin (HP) (p = 0.07) vs. samples from normal bongo (n=37). There were no significant differences in values for total white blood cell counts or for any of the fractions determined by protein electrophoresis. Clinically normal female bongo (n=19) had significantly lower levels of FIB than normal males (n=18) (p=0.014) and this observation was also made with samples from the clinically abnormal group (p=0.004). Many weak to moderate significant correlations were observed with increasing age including increased globulins, fibrinogen, and haptoglobin and decreased A/G ratio and albumin. In clinical cases reviewed in this study, mild HP changes categorized this reactant as a minor APP which contrasts with the major APP classification of HP in the related species of the cow. The preliminary data indicate that the quantitation of these acute phase proteins may offer value in assessing inflammation in this species, but additional studies are needed.